Histoedu, social networks and history of education: pedagogical past from a present perspective - Andrés PAYÀ RICO; Josép M. DUART MONTOLIU; Santiago MENGUAL ANDRÉS (Ediciones Universidad de Salamanca, 2016)
This article presents some preliminary results and considerations about a R&D project about the use of ICTs and social media to do research on educational history. The progress achieved regarding the improvement of social and scientific communication, the significance of the learning process and the motivation shown by the academic community, make us point out the need to consolidate what we have been referring to as history of education 2.0. There are many chances available to learn and to build up knowledge in a shared way, and they challenge us to generate network knowledge and to cooperate in order to: spread our research, get to know other approaches to work, share resources and experiences, exchange information, work collaboratively, etc. We believe in this type of virtual and shared way of working, which has lead us to create HistoEdu, a website to collaborate scientifically and pedagogically regarding the history of education as a discipline.